ZnO Based Material as Photocatalyst for Treating the Textile Anthraquinone Derivative Dye (Dispersive Blue 26 Dye): Removal and Photocatalytic Treatment. (November 2020) - Hussain, Zainab A.; Fakhri, Faten H.; Alesary, Hasan F.; Ahmed, Luma. M.
Abstract: The generation and accumulation of environmental pollutant of industrial contaminations gave it a big challenge to develop many removal strategies of pollution. Textile dyes as dispersive blue 26 dye affected by several decolorization parameters like as temperature, initial pH and initial concentrations of dye. These variables parameter were studied on ZnO-dye suspension solution in dark and photoreaction conditions. In dark reaction, with using thermodynamic and kinetic parameters such as ΔH°, ΔS°, ΔG° and Ea, the type of adsorption was determined and found as a physical adsorption, exothermic and fast reaction. Moreover, the results demonstrated that the photoreaction process under UV-light-A would elevated the rate of reaction, percentage of decolorization and accelerated the half-time of decolorization reaction in 50 ppm of dye. The photoreaction of decolorization of this dye acts as pseudo first order kinetics with endothermic, less random less, non spontenous and fast reaction.